Effective Particle Analysis on Wafer in the EKF-CMP System. (15th February 2021) - Mai, Phuoc-Trai; Lu, Li-Shin; Chen, Chao-Chang A.; Lin,; Yu-Ming
Abstract : This study aims to develop a three-dimensional electro-osmosis flow (3D-EOF) cell model for effective particle analysis on the wafer at steady-state under electro-kinetic force (EKF) assistance during chemical mechanical polishing/planarization (CMP). A simulation software is used to simulate the abrasive particle motion with three functional modules including the electric current, the laminar flow, and the particle trajectories. Parameter designs of various simulation conditions such as electrode gap spacing, direct current voltages, and polishing pad thickness have been investigated to analyze the motion of silica abrasive nanoparticles due to EOF. Simulation results of the EOF velocity of slurry flow circulation in different conditions have compared with theoretical calculation results. Results have shown that the total number of effective particles intensifies significantly with increasing electrode voltage, but decreases in both cases as raising electrode gap and larger pad thickness. Experimental results of EKF-CMP process can improve 25.03%, 2.52 nm, 1.39% for material removal rate (MRR), surface roughness, non-uniformity, respectively. It can explain that the wafer surface polishing qualification is significantly by motion of effectual abrasive particles. Results of this study can be extended to contribute to improvement and optimization of EKF-CMP process for Copper CMP process used in IC fabrication.